Malaysia company law: principles and practice - Mohd. Sulaiman, Aiman @ Nariman; Othman, Effendy (Wolters Kluwer, 2018)
This second edition has been extensively revised and updated in light of the Companies Act 2016, which came into operation on 31 January 2017. It considers an extensive number of reported cases with extracts of significant dicta and relevant statutory provisions, combining the discussion of the Companies Act 2016 and the previous Companies Act 1965. Together with the thoughtful use of tables, diagrams and flowcharts, this publication enables readers to engage in a critical examination of the law as it is and as it ought to be.